Pengaruh Motivasi Berprestasi Terhadap Pemalasan Sosial pada Mahasiswa - Wardani, Trisna; Rusli, Devi (Penerbit Aksara Rentaka Siar (ARS), 2020)
The Effect of Achievement Motivation to Social Loafing in Students. The purpose of the research was to determine how the influence of achievement motivation to social loafing in the majoring in psychology at Padang State University. This research was carried out on Campus V Padang State University in Bukittinggi city. This research was classified as a quantitative research. Sample of this research were 100 respondents psychology Padang State University. The sampling technique of this research was accidental sampling and hypotheses testing was used Simple Regression Analysis. The research found that : The effect of achievement motivation was simultaneously influence to social loafing with significance 0.000 (p<0.05) and that was significance F=14.659